2018
DOI: 10.24059/olj.v22i2.1339
|View full text |Cite
|
Sign up to set email alerts
|

Small Groups in a Social Learning MOOC (slMOOC): Strategies for Fostering Learning and Knowledge Creation

Abstract: Social support and face-to-face learning may enhance outcomes for students who face barriers in accessing Massive Open Online Courses (MOOCs). In this study, we investigated how self-identified volunteer leaders guide and foster interactions among small groups of students who face technical and conceptual barriers in accessing MOOC content. Several months prior to the start of the MOOC (Environmental Education: Trans-disciplinary Approaches to Addressing Wicked Problems), we asked for volunteers among the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…In the nonfacilitated MOOC, however, the relevance of the course contents with the needs of the learners comes out as the major motivating drive as the learners are all students of journalism and need to improve their professional English; however, simultaneously, the absence of a facilitator works as the major cause of failure in registration and completion of the course despite the existence of the stronger relationship between the learners' needs and the course design. Thus, it corresponds with Krasny et al (2018) in finding out that MOOCs that have been facilitated have shown greater completion, motivation, and learning efficacy levels on the part of learners. The respondents from the nonfacilitated MOOC do refer to other issues like unavailability of time and being occupied with the regular academic degree program, but what they emphasize is the technical problems in registration and understanding the required formats for submitting assignments, which could have been solved by a facilitator.…”
Section: Learners' Needs and Course Designsupporting
confidence: 62%
See 4 more Smart Citations
“…In the nonfacilitated MOOC, however, the relevance of the course contents with the needs of the learners comes out as the major motivating drive as the learners are all students of journalism and need to improve their professional English; however, simultaneously, the absence of a facilitator works as the major cause of failure in registration and completion of the course despite the existence of the stronger relationship between the learners' needs and the course design. Thus, it corresponds with Krasny et al (2018) in finding out that MOOCs that have been facilitated have shown greater completion, motivation, and learning efficacy levels on the part of learners. The respondents from the nonfacilitated MOOC do refer to other issues like unavailability of time and being occupied with the regular academic degree program, but what they emphasize is the technical problems in registration and understanding the required formats for submitting assignments, which could have been solved by a facilitator.…”
Section: Learners' Needs and Course Designsupporting
confidence: 62%
“…This study draws on the theoretical approaches of sustainability in sociocultural learning, cognitive behaviorist pedagogies, and online learning behaviors while examining the MOOC that hybridizes in-person and online learning [2,3,10,20]. As learners usually learn more effectively through collaborative and socially cohesive communities, MOOCs also focus on creating such collaborations and communities of peers with diverse participants to ensure effective learning processes [6,11,14].…”
Section: Theoretical Framework and Methodologymentioning
confidence: 99%
See 3 more Smart Citations